Let's go through the steps as outlined and fill in the blanks.
-
Starting with the expression \((24c + 3d) - (6c + 15d)\):
First, we distribute the negative sign:
\[ = 24c + 3d - 6c - 15d \]
-
Next, we group like terms together:
\[ = (24c - 6c) + (3d - 15d) \]
-
Simplifying the grouped terms gives:
\[ = 18c - 12d \]
-
To factor out the greatest common factor (GCF) from \(18c\) and \(-12d\), we find that the GCF is \(6\).
Therefore:
\[ = 6(3c - 2d) \]
In summary, we can rewrite the original expression as follows:
\[ (24c + 3d) - (6c + 15d) = 6(3c - 2d) \]
So the filled-in expression is:
\[ 6(3c + (-2d)) \]
Thus, the complete factored form is:
\[ (24c + 3d) - (6c + 15d) = 6(3c - 2d) \]